2020
DOI: 10.13080/z-a.2020.107.020
|View full text |Cite
|
Sign up to set email alerts
|

Breeding potential of maize landraces evaluated by their testcross performance

Abstract: Significant amounts of crop diversity, especially in out-crossing species like maize (Zea mays L.) is, are often distributed both between and within related groups of accessions. Thus, a detailed characterization and classification of gene bank accessions should be performed prior to use of the best of them for introgression programs to enlarge the genetic base of the elite germplasm pool. Based on performances per se, 40 landraces were chosen out of the wide pool of Western Balkan landraces, previously cluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Considering the stated, it is necessary that climatic conditions are in accordance with biological requirements of plants. In the past ten years, extreme temperatures and disturbances in the amount and distribution of precipitation have significantly affected the reduction of the total production of organic matter and therefore the yield (Hristov et al 2013;Popović et al 2014). Iftikhar et al (2012), indicated that the correlation between the 1000-seed weight and the Table 7.…”
Section: The Correlation Between the Grain Yield And Some Yield Compomentioning
confidence: 99%
“…Considering the stated, it is necessary that climatic conditions are in accordance with biological requirements of plants. In the past ten years, extreme temperatures and disturbances in the amount and distribution of precipitation have significantly affected the reduction of the total production of organic matter and therefore the yield (Hristov et al 2013;Popović et al 2014). Iftikhar et al (2012), indicated that the correlation between the 1000-seed weight and the Table 7.…”
Section: The Correlation Between the Grain Yield And Some Yield Compomentioning
confidence: 99%
“…Moreover, there is huge yet unexploited genetic diversity in maize landraces as a product of thousands of years of evolution under domestication and hybridization [87]. Landraces adapted to local growth conditions could play a significant role in this process [88] and even the smallest participation of local germplasm can have a great impact on the final result [89]. Landraces are a potential source of original traits and new variability [90] desirable to be used in plant breeding programs.…”
Section: Discussionmentioning
confidence: 99%
“…The size of a collection, in terms of the large number of accessions maintained in the gene banks, hinders the efficient selection of desirable genotypes for the improvement of crops through breeding [17]. In order to start and speed up the mobilization of the currently scattered, little studied, and underused maize genetic resources that are maintained in the ex situ Maize Research Institute Zemun Polje (MRIZP) gene bank collection (https: //mrizp.rs/emdb/default.htm, accessed on 15 May 2021), data generated during the longterm pre-breeding programme [4,[18][19][20] were used. Accordingly, 63 early landraces were selected with the following aims: (i) to evaluate their heterotic potential by crossing with two divergent early maturing tester lines, and (ii) to identify the best performing landraces as new sources of early maturity and low grain moisture at harvest.…”
Section: Introductionmentioning
confidence: 99%